Thermal And Structural Analyses Of Roller Compacted Concrete Dams - Bayagoob, Khaled Hamood (2007)

(untitled)
In the present study, a finite element computer code has been developed and is capable for simulating the sequence of construction of the roller compacted concrete dams taking into account the effects of the reservoir water temperature and climatic changes. The probability of cracking can be determined where the variation of the material mechanical properties with time are incorporated using the newly efficient experimental models found in literature. The developed code has been validated first for some numerical examples found in literature. Then the code has been verified against the monitoring temperatures measured by the installed thermocouples in a real case study in Malaysia where good agreement has been obtained between the code predicted results and monitoring temperatures. Then the developed code has been applied for the simulation of sequence of construction and operation phase taking into account the reservoir water operation affects on the upstream dam side. Realistic and identical thermal and structural responses from both the two-dimensional and the three-dimensional models have been obtained. Thus the two-dimensional model can be sufficiently used for the analysis of gravity roller compacted concrete dams without losing or sacrificing the accuracy level. The capability of the developed code has been demonstrated by analyzing a large roller compacted concrete dam of 169 m in height where the impact of the placement schedule on the thermal and structural response has been investigated. The obtained results show that, the placement schedule has significant effect in reducing the tensile stresses at the critical zones of high foundation restraints. Moreover, the developed code has been applied for the determination of the thermal and structural response of an unsymmetrical double curvature arch concrete dam as a general case. The roller compacted concrete technology has been tried as an alternative to the proposed conventional method utilizing the special code for the discretization of the arch dam gorges which was modified in the present study for roller compacted concrete arch dam problem. High tensile stresses at the dam bottom and the abutment boundaries in the upstream side have been observed. In addition to small regions of high compressive stresses near the abutment sides in the downstream side. Thus, a special attention should be paid to these regions in the design of roller compacted concrete arch dams.